Super schoolmaster : Ezra Pound as teacher, then and now - Scholes, Robert, 1929-2016; Ben-Merre, David, 1978- (State University of New York Press, 2021)
Once described by T. S. Eliot as "first and foremost, a teacher and campaigner," Ezra Pound has received no shortage of critical attention. Super Schoolmaster suggests that Pound still has quite a bit to teach readers in the twenty-first century, particularly amid increasing threats to the humanities and higher education. Robert Scholes and David Ben-Merre illuminate Pound's contradictory career of innovative poetics and reactionary politics by following his extensive thinking about teaching and learning within and beyond the academy. Given how scornful Pound could be of institutionalized schooling, the book's title may feel like a misnomer; however, Super Schoolmaster makes clear how wholeheartedly this modernist icon believed in the importance and vitality of learning. Pound's brief flirtation with becoming a professional academic ended early on, but his entire life's work can be seen as an immense pedagogical lesson, promoting a living, breathing culture tied to the very fabric of contemporary life. Not to ignore his critics, who have taught the necessity of reading against Pound, Scholes and Ben-Merre propose that to reread Pound now is to celebrate the joy of learning while always remaining mindful of the ultimate perils of his example.